2015
DOI: 10.1561/105.00000040
|View full text |Cite
|
Sign up to set email alerts
|

Peer Pressure and Moral Hazard in Teams: Experimental Evidence

Abstract: Team incentives have been found to be particularly effective both in the lab and in the field despite the moral hazard in teams problem identified by Holmström (1982). In a newly developed virtual workplace, we show that, in line with Holmström, moral hazard in teams is indeed pervasive. Subsequently, we find strong evidence for the conjecture of Kandel and Lazear (1992) that peer pressure may resolve the moral hazard in teams problem. Organizations equipped with a very weak form of peer monitoring (anonymous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 48 publications
3
43
0
Order By: Relevance
“…Our experimental methodology enables us to control for confounding factors that may have interfered in the empirical evaluation of goal setting policies such as corporate culture, explicit 2 and implicit incentives as well as supervision policies. To that end, we consider a laboratory environment which reproduces several features of field environments while keeping control over the decision environment (Corgnet et al (2013)). Our experimental approach to the analysis of goal-setting is novel in many ways.…”
Section: Work Motivation and Goal Settingmentioning
confidence: 99%
See 3 more Smart Citations
“…Our experimental methodology enables us to control for confounding factors that may have interfered in the empirical evaluation of goal setting policies such as corporate culture, explicit 2 and implicit incentives as well as supervision policies. To that end, we consider a laboratory environment which reproduces several features of field environments while keeping control over the decision environment (Corgnet et al (2013)). Our experimental approach to the analysis of goal-setting is novel in many ways.…”
Section: Work Motivation and Goal Settingmentioning
confidence: 99%
“…The increase in average production levels until period 5 is associated with a corresponding increase in average goals. The decrease in average production levels at the end of the experiment, which may be due to boredom and fatigue (Corgnet et al (2013)), is followed by a decrease in average goals.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…According to Lee's results, the individual performance of agents under a Type I compensation scheme, which is similar to the Japanese model of a high base salary and a low proportion of compensation based on performance, is not significantly better than the individual performance of agents under a Type II compensation scheme, which is similar to the American model of zero base salary and a high proportion of compensation based on performance. Corgnet, Hernan-Gonzalez and Rassenti (2013) found that, with the use of team awards, those individuals entrusted by the organization with peer supervision will exert strong peer pressure to bring organizational production levels to a greater level of productivity.…”
Section: Literature Reviewmentioning
confidence: 99%